Political party institutionalization : a case study of Kenya - Mutizwa-Mangiza, Shingai Price (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2014)
This thesis explores the nature and extent of political party institutionalization in Kenya. More specifically, it focuses on the four dimensions of party institutionalization, namely organizational systemness, value-infusion, decisional autonomy and reification. The study itself is largely located within the historical-institutionalist school of thought, with particular emphasis on the path dependency strand of this theoretical framework. However, the study also employs a political economy approach. It recognizes that the development trajectory of party politics in Kenya did not evolve in a vacuum but within a particular historical-institutional and political-economic context. The thesis advances the notion that those current low levels of party institutionalization that are evident in almost all parties, and the relatively peripheral role that they have in Kenya's governance can be traced to Kenya's colonial and post-colonial political history, the resource poor environment and the onset of globalization.
Keywords: Kenya -- Politics and government; Political parties -- Kenya; Kenya -- History; Kenya -- Colonial influence